Relationship of actigraphy-assessed sleep efficiency and sleep duration to reactivity to stress - Eiman, Matthew N.; Pomeroy, Julia Mary Louise; Weinstein, Ali A. (Sleep Science, 2019)
Objective: Sleep duration is an important predictor of cardiovascular health outcomes, but the role of sleep efficiency is less clear. This study investigated actigraphy-assessed sleep efficiency and sleep duration and their relationship with responses to mental and physical challenge tasks.Methods: To record sleep, actigraph devices were worn on the wrist continuously by 25 participants (age: 33.9±6.9, 60% female) for the duration of a seven-day period. Movement data were used to estimate sleep duration and efficiency. Mental (Stroop test) and physical (cold pressor) challenges were used to assess reactivity to and recovery from stress. During these tasks, heart rate, blood pressure, and emotional states were measured.Results: Significant findings from the mental challenge included a negative correlation between sleep efficiency and reaction time. There were no significant relationships between sleep efficiency and cardiovascular measures during the mental challenge, but sleep duration was related to cardiovascular reactivity. For the physical challenge, sleep efficiency was positively and significantly correlated with blood pressure recovery and sleep duration was not related to any outcome measures.Discussion: Previous literature has focused on sleep duration when assessing sleep and cardiovascular outcomes. However, sleep efficiency may be equally or more important when investigating reactivity to and recovery from stress.
Keywords: Sleep Deprivation; Blood Pressure; Heart Rate; Cardiovascular Disease; Stress, Physiological